Implementasi Media Berbasis Sport Edukasi untuk Meningkatkan Pembelajaran Jasmani Kelas 4 di SD Al Islam Pengkol Jepara - Huda, Ahmad Khoirul; Efendi, Abdullah (Jurnal Porkes, 2025)
The purpose of this study was to determine how effective the use of sport education-based media through snakes and ladders games for students in improving learning achievement in the content of PJOK lessons. The background of this research is based on the low interest and direct involvement in physical learning which has only used conventional media in the form of LKS. This research method is quantitative using a quasi-experimental design. Data were collected using pretest and posttest tests in the form of cognitive physical fitness instruments. The results of homogeneity and normality test data show that it is feasible to analyze parametrically. In the paired sample t-test test there was a significant increase in the learning outcomes of experimental group students (p = 0.000), as well as differences in the independent sample t-test test there were significant differences between the experimental group and the control group. The average posttest score of the experimental group (77.69) was higher than the control (63.17). This finding shows that the snakes and ladders game based on sport education actively contributes to improving learning outcomes which include cognitive, active participation, and motor skills of students in learning PJOK. This media can be an innovative and fun alternative when learning physical education in elementary schools.